Analisis Sentimen Investor terhadap kinerja saham syariah di Indonesia selama masa pandemi Covid-19 - Rizki Fadhel; Fajri Adrianto; Mohamad Fany Alfarisi (Politeknik Ganesha Medan, 2022)
The COVID-19 pandemic has become a concern regarding the severity of the pandemic and has an important role in investment decisions. Investment decisions are influenced by news (noise trader) circulating in the capital market. In this study, we analyze investor sentiment on the performance of Islamic stocks in Indonesia during the 2020-2022 Covid-19 pandemic. The independent variables in this study used Google Trend as a search for the number of words 'covid' and 'crisis, trading volume, and the Consumer Confidence Index. Meanwhile, stock returns are used as the dependent variable. The sampling technique was carried out by purposive sampling to obtain 20 companies that were used as research samples. The analytical technique used in this study is panel data regression, where the results obtained are sentiment based on google trends with the word 'covid' having a significant and positive effect, trading volume and CCI also have a significant effect on stock returns. However, the word 'crisis' has no significant effect on stock returns.